Complexity, transdisciplinarity and networks: towards the collective construction of a new university (Polis (Santiago), 2018)
The article argues on the need for interdisciplinary and integrative visions in order to represent a social organization as complex as the university, starting from its current state of fragmentation. For the author, Unam is the most notorious referent of this need. It also proposes to re-link the different knowledges in order to create a decentralized intelligence that would facilitate the design and construction of a new university, from a text approached from perplexity, doubt, and the challenge of adventure, hoping to inspire a synergy from what might seem a utopia.
Keywords: interdisciplinarity; university; utopy